DESTRUCTION MECHANISMS OF CU-ETP COPPER GUIDES FOR SECTIONAL INSULATORS OF RAILWAY TRACTION - Jarosław KONIECZNY (Scientific Journal of Silesian University of Technology. Series Transport)
This article presents the results of a research on the operational damage to sectional insulator guides made of hard electrolytic copper Cu-ETP (Electrolytic Tough Pitch Copper). The guides were used on various rail routes, in real conditions, on which the trains ran at maximum speeds between 40 and 120 km/h for periods of 6 or 12 months. The microstructure of the surface, the working layer of the guide, which contacts the graphite plate of the current collector and the cross-section of the guide in the place where it was damaged was examined using the Olympus light microscope. The analysis of the chemical composition in the EDS micro-regions was performed using the Zeiss Supra 53 scanning electron microscope (SEM), while the qualitative X-ray phase analysis was performed with the use of the Panalytical X'Pert diffractometer. Scratches and deformations of the surface layer characteristic of the phenomenon of friction caused by the current collector were observed in the microstructure of the damaged parts of the guides of section insulators. The effect of a very intense oxidation process was also observed, as well as the effects of an electric arc, which according to the author, is the factor that has the most destructive effect on the condition of the guides.